Peran Mediasi Budaya Organisasi dalam Memperkuat Resiliensi Manajemen Perguruan Tinggi - Diki Akhwan Mulya; I Made Sumertajaya; Anggraini Sukmawati (IPB University, 2023)
Resilience is the ability to survive, adapt, rise, and recover from unexpected conditions. The Covid-19 pandemic is unpredictable for almost all organizations, including Bogor Agricultural University (IPB), one of the state universities in Indonesia with legal status (PTN-BH). The study analyzes the effect of strategic human resource management (SHRM) on the resilience of university management in facing the COVID-19 pandemic, mediated by organizational culture. Respondents in this study were lecturers and education personnel at Bogor Agricultural University (IPB). The sampling technique used a stratified random sampling technique, obtaining 358 respondents. The research data were obtained by survey method using an online questionnaire. Data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results showed that organizational culture successfully mediated the effect of SHRM on organizational resilience positively and significantly. Strategic HRM latent variables have a positive and significant impact on organizational culture, and organizational culture has a positive and significant impact on organizational resilience. The direct effect of SHRM on organizational resilience is positive and effective according to lecturers but not substantial according to education employees. This result means that the strategic HR policies implemented can support lecturers in adapting to changing conditions to continue to carry out their duties and achieve their performance targets. Meanwhile, for education employees, existing policies that have yet to help tend to contribute significantly to efforts to achieve organizational resilience. Education employees requires strategic HRM policy support that is different from lecturers to be able to contribute significantly to the achievement of organizational resilience.